2010
DOI: 10.1016/j.bbadis.2009.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Pathological roles of MAPK signaling pathways in human diseases

Abstract: The mammalian family of mitogen-activated protein kinases (MAPKs) includes extracellular signal-regulated kinase (ERK), p38, and c-Jun NH(2)-terminal kinase (JNK), with each MAPK signaling pathway consisting of at least three components, a MAPK kinase kinase (MAP3K), a MAPK kinase (MAP2K), and a MAPK. The MAPK pathways are activated by diverse extracellular and intracellular stimuli including peptide growth factors, cytokines, hormones, and various cellular stressors such as oxidative stress and endoplasmic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
1,406
2
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,022 publications
(1,447 citation statements)
references
References 177 publications
31
1,406
2
8
Order By: Relevance
“…In fact, relatively small changes are perhaps not unexpected, as more substantial changes in expression of these proteins are associated with oncogenic, apoptotic, and excitotoxic events (Huang et al, 2009;Kim and Choi, 2010;Soriano et al, 2008;von Engelhardt et al, 2007;Wagner and Nebreda, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…In fact, relatively small changes are perhaps not unexpected, as more substantial changes in expression of these proteins are associated with oncogenic, apoptotic, and excitotoxic events (Huang et al, 2009;Kim and Choi, 2010;Soriano et al, 2008;von Engelhardt et al, 2007;Wagner and Nebreda, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…So, it was suggested that suppression of ionization of multiply phosphorylated peptides by mono-phosphorylated peptides on MS was reduced in the samples prepared by the 4-step elution method. In addition to the enhanced resolution of mono-phosphorylated peptides, the stepwise elution method was especially useful for identification of multiply phosphorylated sites that may be linked to the receptor signalling process because kinases involved in the process often require multi-site Xenopus egg phosphoproteome phosphorylation for their activation (18,19). A fully automated phosphopeptide purification system involving optimized 4-step elution from a titania column is more useful than the original 1-step method for lessbiased phosphoproteome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking ERK1/2 activation reduces mechanical and/ or thermal hypersensitivity following tissue injury/inflammation [8,10,11]. Phosphorylated ERK1/2 have a series of downstream targets including the mitogen-and stress-activated kinases 1 and 2 (MKS1/2) [12]. However, the ERK1/2 activation-induced transcriptional changes appear to be mediated predominantly by MSK1/2 [13,14].…”
Section: J Pharm Res Drug Des 2017 | Vol 1:101mentioning
confidence: 99%